Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1002/we.1655
|View full text |Cite
|
Sign up to set email alerts
|

An upper size of vertical axis wind turbines

Abstract: An upper size of vertical axis wind turbines.Wind Energy, 17 (10) ABSTRACTThe scaling behaviour of a straight-bladed vertical axis wind turbine is considered. A scaling scheme is described that, in the presence of a wind shear profile, aims at leaving the material stresses of the scaled construction unchanged. Based on a recent 200 kW three-bladed H-rotor design, a structural upper size of the turbine is proposed, this size being the scale at which the gravitational force starts to become important. As gravit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…VAWTs typically have fewer moving parts and a generator located at ground level, which could ultimately lead to lower maintenance cost and higher availability . Also, in Ottermo and Bernhoff it has been shown that the concept is more suitable for upscaling than the HAWT concept. Furthermore, the VAWT concept has potentially lower noise emission …”
Section: Introductionmentioning
confidence: 99%
“…VAWTs typically have fewer moving parts and a generator located at ground level, which could ultimately lead to lower maintenance cost and higher availability . Also, in Ottermo and Bernhoff it has been shown that the concept is more suitable for upscaling than the HAWT concept. Furthermore, the VAWT concept has potentially lower noise emission …”
Section: Introductionmentioning
confidence: 99%
“…VAWTs typically have fewer moving parts and a generator located at ground level which could ultimately lead to higher availability and lower maintenance cost [1]. Furthermore, it has been shown that the concept is more suitable for up-scaling than the HAWT concept [2]. Moreover, of special interest here, VAWTs has potentially lower noise emission [1].…”
Section: Introductionmentioning
confidence: 99%
“…It is a technology that has received an increased interest recently, especially for offshore applications due to its low center of gravity [1][2][3]. The technology has the potential to scale to large sizes as shown by Ottermo and Bernhoff [4]. A comparison between a horizontal axis wind turbine (HAWT) and a VAWT by Eriksson et al concluded that the VAWT can be built with less moving parts and that the straight-bladed Darrieus design has manufacturing benefits compared to the curved Darrieus turbine [5].…”
Section: Introductionmentioning
confidence: 99%